Linking Activation of Microglia and Peripheral Monocytic Cells to the Pathophysiology of Psychiatric Disorders - Takahashi, Yuta; Yu, Zhiqian; Sakai, Mai; Tomita, Hiroaki (Frontiers in Cellular Neuroscience, 2016)
A wide variety of studies have identified microglial activations in psychiatric disorders, such as schizophrenia, bipolar disorder, and major depressive disorder. Relatively fewer, but robust, studies have detected activations of peripheral monocytic cells in psychiatric disorders. Considering the origin of microglia, as well as neuropsychoimmune interactions in the context of the pathophysiology of psychiatric disorders, it is reasonable to speculate thatmicroglia interact with peripheral monocytic cells in relevance with the pahogeneses of psychiatric disorders; however, these interactions have drawn little attention. In this review, we summarize findings relevant to activations of microglia and monocytic cells in psychiatric disorders, discuss the potential association between these cell types and disease pathogenesis, and propose perspectives for future research on these processes.